Comparison of Suffolk, Texel and Charollais sired lambs for slaughter traits under upland grassland conditions of the north east England - YAQOOB, M; MERREL, B G; AKHTAR, P; NAWAZ, H; SULTAN, J I; MUSTAFA, M I (The Indian Journal of Animal Sciences, 2010)
Performance data on growth of lambs were collected for 3 years from crossbred females and castrated male progeny of three terminal sire breeds, namely Charollais, Suffolk, and Texel, out of Mule ewes (Bluefaced Leicester sires × Scottish Blackface or Swaledale dams) reared under upland grassland conditions in the north-east of England and were analyzed by general linear regression method using Genstate. The least square means for slaughter and carcass weights of Suffolk, Texel and Chairollais sired lambs were 42.023a±0.16 kg and 18.27a±0.08 kg; 40.277±0.164 and17.89±0.08; 41.247±0.16 and 18.21±0.08 respectively. Similarly slaughter age, killing out percentage and conformation of the lambs were compared as well. This study suggests that the breed of sire, year of lambing and sex of lamb can affect slaughter and carcass weights of lambs, and these factors require careful consideration in practical lamb husbandry.